Art's agency and art history - Osborne, Robin; Tanner, Jeremy, 1963- (Malden, MA : Blackwell Pub., 2007)
- Introduction: Art and agency and art history / Jeremy Tanner and Robin Osborne##- Enchantment and sacrifice in early Egypt / David Wengrow##- Agency marked, agency ascribed : the affective object in ancient Mesopotamia / Irene J. Winter##- Portraits and agency : a comparative view / Jeremy Tanner##- The agency of, and the agency for, the Wanli emperor / Jessica Rawson##- The material efficacy of the Elizabethan jewelled miniature : a Gellian experiment / Jessen Kelly##- Representational art in ancient Peru and the work of Alfred Gell / Jeffrey Quilter##- Gell's idols and Roman cult / Peter Stewart##- Sex, agency and history : the case of Athenian painted pottery / Robin Osborne##- Abducting the agency of art / Whitney Davis.
Includes bibliographical references and index.
boek